Analisis Kepatuhan terhadap Fatwa Dewan Syariah Nasional Tentang Wakalah, Hawalah, dan Kafalah Dalam Kegiatan Jasa Perusahaan Pembiayaan Syariah - Darwin Darwin; Saparuddin Siregar (Politeknik Kutaraja, 2020)
The objective of this research is to analyze compliance of the Fatwa Dewan Syariah nasional (Syariah National Board) concerning Wakalah, Hawalah, and Kafalah so that whether it can be applied in the activities of islamic finance company. This is a juridical normative research and focused on analyzing secondary data, specifically in 2 (two) types of Legal material, Primary and Secondary Legal Materials. Furthermore, all data will be analyzed and presented descriptevely. This research shows that, regarding Wakalah, the Fatwa about Wakalah and Wakalah bil Ujrah are in conformity with activities by Islamic Finance Company Service. Wakalah was used as Complementary Agreement in Murabahah Financing with Islamic Finance Company as Principal. In the other side, Fatwa concering Wakalah bil Ujrah used when Islamic Finance Company take a position as Guarantee. Even though Financial Service Authority’s Regulation specify that service activities may use Hawalah and Kafalah Agreement, but based on this research’s analysis about Fatwa and Fikih, only Hawalah bil Ujrah and Kafalah bil Ujrah that may be used by Islamic Finance Company